Bedside Evaluation for Early Sepsis Intervention: Addition of a Sepsis Response Team Leads to Improvement in Sepsis Bundle Compliance - Sally Suliman, MD; John Price, DO; Meredith Cahill, MPH; Taylor Young, MPH; Stephen Furmanek, MPH; Juan Galvis, MD; Hugh Shoff, MD; Frankie Parra, BSN; Gina Stevenson, BSN; Rodrigo Cavallazzi, MD (Critical Care Explorations, 2021)
Objectives:. Sepsis is associated with high morbidity and mortality and high healthcare costs. We hypothesized that a multifaceted quality improvement project would lead to an improvement in compliance with the sepsis “bundles.” Design:. Patients presenting to the emergency department that met criteria for sepsis at triage triggered notification of an emergency department physician and the sepsis response team in order to facilitate timely completion of the 3-hour bundles. The primary outcome was compliance with the seven sepsis bundle components. Secondary outcomes included all-cause inhospital mortality, hospital length of stay, and time in the emergency department. Setting:. The study was conducted at a 404-bed tertiary academic medical center over a 2-year period. Patients OR SUBJECTS:. The study included patients that presented to the emergency department that met criteria for sepsis. MEASUREMENTS OR Main Results:. The study included 163 patients. Overall compliance with the sepsis bundle was 79% (95% CI, 72–84%). There was significant improvement in comparison with the hospital’s historical compliance of 37% (p < 0.001). Compliance with the individual bundle components ranged from 80% to 100%. Sixteen patients died (10%) in the hospital. There was no statistically significant difference between the compliant and noncompliant groups regarding the secondary outcomes of length of stay or inhospital mortality. Conclusions:. This study found that implementation of a sepsis response team can improve compliance with completion of sepsis bundles. This indicates that it is feasible to implement a multidisciplinary quality initiative to improve timely treatment of patients with sepsis at an academic center using a resident-driven sepsis response team.